KETERTARIKAN MINAT MAHASISWA MEMILIH PROGRAM STUDI S1 AKUNTANSI - Tiara Diva Permata; Pancawati Hardiningsih (Jurnal Riset Akuntansi Politala, 2023)
Abstract This study aims to determine the effect of educational costs, socioeconomic status and motivation on the interest in choosing an undergraduate accounting study program. This type of research is quantitative research using primary data and distributing questionnaires via the Google form. The population in this study were students of the S1 Accounting study program at tertiary institutions who had accreditation A in the city of Semarang. The sample in this study were students of the S1 accounting study program for the 2019-2022 period who were still active. The sampling method used was purposive convenience sampling and a total of 119 students were obtained. The data analysis technique uses multiple linear regression analysis. The results of the study show that educational costs and motivation have a positive and significant effect on students' interest in choosing an undergraduate accounting study program, while socioeconomic status has no effect on students' interest in choosing an undergraduate accounting study program.